(untitled) (Research, Society and Development, 2023)
The objective was to identify the types of designs used in experiments to evaluate milk production, through a systematic search of studies published in the Revista Brasileira de Zootecnia (RBZ) over a period of 10 years. An electronic search was carried out for articles published in the RBZ, which evaluated the production of goat or bovine milk in the period from 2010 to 2019. With this, the articles found were divided into two groups, research with bovine milk production and research with goat milk production. In each article, the types of experimental designs used were evaluated. After being identified, the data were compiled and systematized using a Microsoft Excel® spreadsheet. Subsequently, the data were organized using descriptive statistics and submitted to correlation tests. In addition, a comprehensive review of each identified design was performed. The designs used in the studies were the Latin square (QL), in 21% (double = 21%; triple = 23%; four = 4%) of the studies, followed by the randomized block design (DBC) with 11%, completely randomized design (DIC) with 11%, factorial with 4% and split plots (P.SUB) with only 2%. QL with 9% (double = 9%; triple = 18%; four = 9%); followed by DIC with 28%, P.SUB with 18% and factorial with 9%. Thus, analysis of variance is fundamentally applied to measure differences between treatments in experimental trials.